2013
DOI: 10.1002/pen.23701
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial time‐dependent ratcheting behavior of bronze powder filled polytetrafluoroethylene at room and high temperature

Abstract: A series of tensile and ratcheting experiments for cold compaction polytetrafluoroethylene (PTFE) and bronze filled PTFE (PTFE/bronze) were conducted with Dynamic Mechanical Analyzer (DMA‐Q800) at room and high temperature (473 K). The effects of peak stress‐holding time, creep, recovery, mean stress history, stress‐rate history, and pretension on the ratcheting behavior of PTFE/bronze were investigated. It is found that longer peak stress‐holding time leads to larger ratcheting strain accumulation. In the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…7), it is concluded that: (1) the ratcheting of the PC-7030PJ and PC-7020PJ polymers is significantly time-dependent, and the ratcheting strains produced in the load cases with a longer hold-time at peak stress points and at a lower stress rate are larger than those with a shorter hold-time and at a higher stress rate, respectively. The time-dependent ratcheting of PC-7030PJ and PC-7020PJ polymers is similar to that observed for other materials [13,18]. (2) The time-dependent ratcheting of the PC-7030PJ polymer with a larger molecular weight is more remarkable than that of the PC-7020PJ polymer with a smaller molecular weight, as shown in Figs.…”
Section: Time-dependent Ratchetingsupporting
confidence: 78%
See 2 more Smart Citations
“…7), it is concluded that: (1) the ratcheting of the PC-7030PJ and PC-7020PJ polymers is significantly time-dependent, and the ratcheting strains produced in the load cases with a longer hold-time at peak stress points and at a lower stress rate are larger than those with a shorter hold-time and at a higher stress rate, respectively. The time-dependent ratcheting of PC-7030PJ and PC-7020PJ polymers is similar to that observed for other materials [13,18]. (2) The time-dependent ratcheting of the PC-7030PJ polymer with a larger molecular weight is more remarkable than that of the PC-7020PJ polymer with a smaller molecular weight, as shown in Figs.…”
Section: Time-dependent Ratchetingsupporting
confidence: 78%
“…3, it is seen that: (1) apparent ratcheting occurs during the cyclic tests of both the PC-7030PJ and PC-7020PJ polymers. The ratcheting strain increases with the number of cycles in the direction of tensile mean stress, while the ratcheting strain rate decreases rapidly in the first beginning of cyclic loading and a stable ratcheting with a constant ratcheting strain rate is reached after certain cycles, which is similar to that observed in the cyclic tests of other polymer materials [13][14][15][16][17][18].…”
Section: Effects Of Stress Levelssupporting
confidence: 72%
See 1 more Smart Citation
“…For example, Chen et al investigated the uniaxial ratcheting behavior of PTFE under cyclic compression and constructed a simple constitutive model with stress rate effects (Chen and Hui, 2005;Zhang et al, 2008). Other polymer materials have also been investigated by various authors (Yu et al, 2008;Wang et al, 2010;Shariati et al, 2012;Avanzini, 2008;Liu et al, 2008;Li et al, 2013;Xu et al, 2014). The effect of thermal cycling aging on materials and structures has been adequately documented to improve the stability and reliability of the components Pang et al, 2001;Chiu et al, 2002;Jang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%